The superradiance of a bunch of rotating electrons - Kuklin, V.M.; Litvinov, D.N.; Sporov, A.E. (Вопросы атомной науки и техники, 2018)
Equations describing the excitation of a TE wave by a beam of electrons rotating in an external magnetic field in a waveguide in two regimes were considered. In the first regime the interaction of the oscillators − rotating electrons in the magnetic field − was neglected. It was assumed that the beam electrons interact only with the waveguide modes. In the second case, in the superradiance regime, the beam electrons interact with each other due to their spontaneous radiation. In the article the basic features of the description of the gyrotron gain regime are discussed.